Fertility In Women With Autoimmune Thyroiditi (Eurasian Medical Research Periodical, 2025)
This article focuses on autoimmune thyroiditis (also known as Hashimoto's thyroiditis), a chronic condition in which the immune system mistakenly attacks the thyroid gland, leading to inflammation and hypothyroidism. This condition significantly affects fertility, particularly in women, who may experience difficulties in conceiving. The article examines the main fertility-related issues faced by women with autoimmune thyroiditis, including hormonal imbalances, irregular menstrual cycles, reduced egg quality, increased risk of miscarriage, and premature birth. Diagnostic methods, including tests for thyroid hormone levels and antibodies, are discussed, along with treatment approaches such as hormone replacement therapy with levothyroxine. The article also explores the use of assisted reproductive technologies, such as in vitro fertilization (IVF), with a focus on the importance of normalizing thyroid function and monitoring antibody levels. The conclusion emphasizes that with proper treatment and monitoring, many women with autoimmune thyroiditis can successfully conceive and carry a healthy pregnancy to term.